Application of microsecond pulsed glow discharge to modern commercially available optical emission spectrometers for bulk elemental analysis 1. Issue 4 (23rd March 2018) - Voronov, M.; Hoffmann, V.
Abstract : Microsecond Pulsed Glow Discharge (μs-PGD) was applied to commercially available spectrometers specified for OES elemental analysis with Grimm type sources, in order to have a look at the benefits which PGD can bring for practical bulk analysis. Abstract : Microsecond Pulsed Glow Discharge (μs-PGD) was applied to commercially available spectrometers specified for OES elemental analysis with Grimm type sources, in order to have a look at the benefits which PGD can bring for practical bulk analysis. Intensities of more than 70 spectral lines of different elements together with background and noises were compared between μs-PGD and continuous Glow Discharge (GD) using CCD and PMT detectors. In comparison to continuous GD, the detection limits with PGD were 1.5–14 times lower for different spectral lines. The reasons for such a moderate improvement are discussed.